Innovation and Sustainable Tourism: reflections of the state-of-the-art in the period 2010-2017 : Inovação e Turismo Sustentável: reflexões do estado da arte no período de 2010 a 2017 - Martins-Rodrigues, Maria Carolina; Barbieri da Rosa, Luciana Aparecida; Damke, Luana Ines; Godoy, Tais Pentiado; Gomes, Clandia Maffini (Revista de Turismo Contemporâneo, 2020)
This article aims to launch the publications on Strategic Innovation Management and Sustainable Tourism, part of the research in the Web of Science database of ISI Web of Knowledge. Thus, the objective of this article is to analyse as characteristics of the publications related to the theme Strategic Management and Sustainable Tourism in the period from 2010 to 2017, totalling 199 selected articles. The methodology used for this study, is a bibliometric and descriptive research. The survey results show the year with the highest number of publications was 2016 (44). Journal of Sustainable Tourism presented the highest number of publications with a total of 20. Keywords: Bibliometry. Innovation. Sustainable Tourism.